2021
DOI: 10.1177/0973005221991603
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Factors That Affect Inclusive Businesses: The Case of Banana Cooperatives in the Magdalena Region (Colombia)

Abstract: Inclusive business as a model at the base of the pyramid is a relatively recent unit of study in academic literature. From the institutional perspective, businesses are affected by norms, processes, rules of moral and ethical behaviour, which have not been studied for the base of the pyramid in inclusive businesses, much less in agricultural cooperatives. The objective of this research is to identify institutional factors that can affect agribusiness inclusive models. In this research, agricultural cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 81 publications
(113 reference statements)
0
1
0
1
Order By: Relevance
“…One of the primary reasons for low income through agriculture-related activities for rural people is poor market linkages (Kumari, Bharti, and Tripathy 2021). Dobryagina (2019) suggested that non-hereditary entrepreneurs contribute more towards rural development than hereditary entrepreneurs (Maestre-Matos et al 2021). Nemes et al (2021) studied alternative and local food systems in 13 countries and concluded that boosting social innovation with the help of technological innovation will promote local food consumption at the time of this pandemic when supply chain systems have been badly affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the primary reasons for low income through agriculture-related activities for rural people is poor market linkages (Kumari, Bharti, and Tripathy 2021). Dobryagina (2019) suggested that non-hereditary entrepreneurs contribute more towards rural development than hereditary entrepreneurs (Maestre-Matos et al 2021). Nemes et al (2021) studied alternative and local food systems in 13 countries and concluded that boosting social innovation with the help of technological innovation will promote local food consumption at the time of this pandemic when supply chain systems have been badly affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algunas investigaciones muestran que el sector agrícola tiene condiciones que facilitan el desarrollo de negocios inclusivos NI, tomando como BdP a los pequeños productores (L. German et al, 2018;L. A. German et al, 2020;Kelly et al, 2015;Schouten & Vellema, 2019) y tratan de explicar el papel de estos productores en la cadena de valor agrícola (Maestre- Matos, 2021;German et al, 2020). En la tabla 1 se evidencian algunas características particulares que diferencian los negocios inclusivos en el sector agrícola de los modelos de negocio tradicionales.…”
Section: Conceptosunclassified
“…En este caso, los pequeños productores son los encargados del proceso de precosecha, cosecha y poscosecha, aportando el 34,35% de la producción de banano del sector en Colombia (UPRA, 2020). Esta población se caracteriza por tener un bajo nivel de formación (el 69% de los trabajadores no tiene educación formal, el 17% terminó la primaria, el 12% terminó el bachillerato y el 1% tiene otros estudios) (Maestre Matos et al, 2019), carencia de servicios públicos (la zona donde se ubican no cuenta con un sistema de alcantarillado para desechos y residuos, y hay deficiencias e irregularidades en el suministro de agua), sistema de comunicación deficiente y sistema de transporte irregular; mostrando bajos niveles de satisfacción de necesidades básicas (Maestre- Matos et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…В своих работах M. Маэстре-Матос и соавторы выделяют институциональные факторы развития кооперативов, обращая внимание на необходимость интеграции формальных и неформальных факторов. К формальным факторам относятся сертификаты, стандарты качества, политика социальной ответственности и экономические стимулы; к неформальным -сотрудничество, повышение качества жизни, укрепление социальной ренты [Maestre-Matos et al, 2021].…”
Section: Introductionunclassified